P 152 Self-reflection on illusions and mental health in emergency medicine. Issue 10 (October 2017) - Spiegel, R.; Sutter, R.
Abstract : Introduction: It is a well known fact that sleep deprivation may similarly affect judgment as alcohol or drugs (Philip et al., 2001 ). The following example describes an emergency physician who doubts his mental health, knowing that he is sleep-deprived. Subsequently, an analogy will be formed to daily clinical practice. Case presentation: On a Friday evening, after seeing many emergency patients in the outpatients' clinic of a Swiss academic tertiary medical care centre, a physician drove to his fiancée who lived 260 km north in Heidelberg (Germany). An hour past midnight, after having driven for approximately 160 km, the physician suddenly faced a four-legged, hairy creature which he assumed to be a dingo passing his car on the German motorway A5. He did not expect a dingo, as he was aware that they do not exist in Europe. Nevertheless, he informed the local police about the animal, fearing it could get hurt. The physician considered several differential diagnoses. Could the animal have been a wolf, though wolves were known to be extinct for 150 years in this region. Or could the animal be a stray dog, a deer, an illusion due to fatigue (Philip et al., 2001 ), impaired vision (Jacob et al., 2004; Teunisse et al., 1996 ) or night-vision, though the physician never had experienced such phenomena before. He was certain that he had no risks for complex optical illusions or hallucinations, such as alcohol- or drug-related hallucinations, having a hallucinogen persisting perception disorder, an ocular disease, migraines, or a head trauma. The workup of this case shed light into the dark, confirming that it was a wolf who had been run over by another car, which was the first encounter with a wolf in Southwest Germany for 150 years (Deutsche Presse Agentur, 2015 ). Discussion: Self-reflection about mental health is a good idea among physicians, especially in the context of long working-hours and possible burnout. At the same time, emergency physicians should trust their perception, however bizarre the first impression might be. The perception should not be downplayed or ignored. The solution is to combine both, self-reflection about mental health and vigilance to spot bizarre and unusual things. It is important to apply a working diagnosis with a double-check by a colleague in the emergency department. While the presumed initial diagnosis (dingo) proved to be wrong, it came considerably close to the final diagnosis (wolf). This resembles daily practice in the Emergency Department, where a patient is admitted with a working diagnosis and the final diagnosis gets established during the hospital stay.